Simultaneous Determination and Validation of Enalapril Maleate, Hydrochlorothiazide and Paracetamol in Combined Tablet Dosage Form Using RP-HPLC Method - Dubey, Nitin; Jain, Ankit; Sardiya, Jinendra; K. Jain, Dinesh (Asian Journal of Chemistry, 2012)
A simple, accurate and precise RP-HPLC method has been developed for the simultaneous estimation of enalapril maleate, paracetamol and hydrochlorothiazide in commercially available tablet formulations. The chromatographic separation was achieved on Luna C8 column using mobile phase acetonitrile:phosphate buffer:triethylamine (20:79.1:0.1 % v/v/v) (pH 4 ± 0.1) as mobile phase at a flow rate of 1.0 mL/min. Quantitation was carried out at lmax of 215, 245 and 270 nm for enalapril maleate, paracetamol and hydrochlorothiazide, respectively. The method was validated as per ICH guidelines. The method may be applied for the routine simultaneous estimation of the above mentioned drugs in tablet dosage form.